1995
DOI: 10.1111/j.1745-4530.1995.tb00366.x
|View full text |Cite
|
Sign up to set email alerts
|

ADSORPTION of BILE ACIDS ON CEREAL TYPE FOOD FIBERS

Abstract: A study involving measurement and analysis of adsorption of common bile acids, namely cholic, deoxycholic, and lithocholic acids, on cereal type dietary fibers was conducted. the selected food fibers were oat fiber, rice fiber, barley fiber, corn bran, and wheat bran, which are all extensively used in processed foods. the adsorption data were measured at 37C and 25C, which correspond to approximate human body and room temperatures. Influence of particle size reduction, due to grinding, on a fiber's bile acid b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…This increase was attributed to increased surface area available for adsorption due to micropore openings. The trends noted by Huang and Dural (1995) for bile acids were opposite to our results for WAI.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This increase was attributed to increased surface area available for adsorption due to micropore openings. The trends noted by Huang and Dural (1995) for bile acids were opposite to our results for WAI.…”
Section: Resultscontrasting
confidence: 99%
“…Both corn and wheat brans showed an increase in adsorption of bile acids when particle size was reduced (Huang and Dural 1995) but oat bran showed only a minimal increase. This increase was attributed to increased surface area available for adsorption due to micropore openings.…”
Section: Resultsmentioning
confidence: 97%
“…Kern et al reported that fiber exhibits greater binding for dihydroxy bile acids (chenodeoxycholic acid) than trihydroxy bile acids (cholic acid) [33]. Thus, adsorption of bile acids by dietary fiber will be dependent on both the hydrophobicity [34].…”
Section: Discussionmentioning
confidence: 98%
“…Three methods as mentioned above were used for analysis of antioxidant activities and final values represent average of triplicate determinations. Alpha-amylase inhibition and bile acids binding ability of samples were determined as described earlier (6,10). For both alpha-amylase inhibition and bile acid binding ability, the samples were run in triplicate and averaged.…”
Section: Determination Of Bioactive Potentialmentioning
confidence: 99%